Semantic Errors in Indonesian Literary Texts: A Case Study of Pleonasm, Ambiguity, and Diction in Lentera Padam - Rokhan, Sabrina Zerlinda; Aranaia, Vika (IAIN Parepare, 2025)
Language is a very important daily communication tool, communication can be hampered by language errors. This research discusses semantic errors in the short story “Lentera Padam” by Faisal Fajri. This research uses descriptive qualitative method by reading and recording important things related to semantic errors that will be examined. The purpose of this research is to identify semantic errors. The analysis of this research focuses on semantic errors, namely the symptoms of pleonasm, ambiguity and the use of words or diction that are less precise Based on the results of the analysis, it is known that there are semantic errors such as equilibrium, psychic, pajang etc.